THE IMPLEMENTATION OF KODIM 0204/DS SOCIAL COMMUNICATION IN PREVENTING RADICALISM IN DELI SERDANG - Rakhmat Shaleh Siregar; Bambang Wahyudi; Haposan Simatupang (Indonesia Defense University, 2019)
The current spread of radicalism has attacked all levels of society, especially the younger generation, which if not immediately prevented, will pose a threat for the stability and security in Indonesia, including in Deli Serdang. Kodim 0204/DS is a Teritorial Unit whose one of main duties is to carry out territorial development. Territorial development is carried using Social Communication method, TNI Service and Regional Resistance Development. This study is designed to gain an understanding of the implementation of Social Communication activities in preventing radicalism. This study aims to: first, analyze Social Communication by Kodim 0204/DS in Deli Serdang; second, analyze the implementation of social communication by Kodim 0204/DS in preventing radicalism in Deli Serdang. This study employs qualitative methods. The data were obtained through observation, interviews, documentation and triangulation. Data analysis techniques were mostly performed in conjunction with the data collection during field visit. Research sites is in Deli Serdang. This study finds that: 1) Social Communication can theoretically be implemented according to existing territorial development program even though its implementation is not optimal and needs to be improved on aspects that support communication processes, i.e. sources, messages, media, recipients, influences, feedback and environment; 2) The implementation of Social Communication is supported by means, ways and ends, namely to prevent radicalism in Deli Serdang. Social Communication by Kodim 0204/DS in preventing radicalism can be implemented but needs to be improved. This study recommends the optimization of elements that support communication process.Keywords: Implementation, social communication, prevention, radicalism